ANXIETY OF AUGUST RUSH IN AUGUST RUSH MOVIE BY KRISTEN SHERIDAN (2007): A PSYCHOANALYTIC APPROACH - NOVITASARI, AZZAHRA (2011)
The study is to reveal how anxiety is reflected in August Rush movie directed by Kristen Sheridan in 2007. The objectives of the study are to analyze the structural elements of the movie in order to identify the unity of the movie and to analyze of the major character using psychoanalytic approach. The object of the study is a movie August Rush by Kristen Sheridan. In this research the writer employs the descriptive analysis as a type of the research. The data sources are divided in two, namely primary data sources that are taken from the text of the movie such as dialogues, character action and whole narration which are relevant to the object of analysis. The secondary data source includes the reference from some books and internet. The methods of collecting data are observation and library research. The technique of analyzing data is descriptive. The result of the analysis shows that firstly, based on the structural analysis, it is clear that in this movie, director wants to deliver a moral message that it requires a sense of danger in order to make an individual realize the reasonability of his or her own personality in social interaction. Secondly, the psychoanalytic analysis shows that anxiety develops out of a conflict between id, ego, and superego resulting in different types of anxieties.